TREATMENT AND PREVENTION OF PURULENT-NECROTIC COMPLICATIONS AFTER AMPUTATION OF THE LOWER EXTREMITIES - Alisher O. Okhunov (Central Asian Journal of Medicine, 2024)
Transfemoral amputation of a limb performed by a patient with obliterating atherosclerosis with irreversible ischemia is a difficult, traumatic operation and is accompanied by high mortality. High mortality after amputation of a limb at the hip level is associated with the severity of the general condition of patients and complications of the postoperative period. As our studies have shown, the most common complication after limb amputation is an infection of the femoral stump wound, its development is directly related to metabolic disorders in patients, a decrease in the immune status, ischemia of the stump tissues and foci of secondary infection. The clinical picture of infection of the femoral stump wound is variable. It depends, first, on the general condition of the patient, the spread of the process, the trophism of the stump tissues, and the nature of the microflora. Improving the treatment results of patients who have undergone limb amputation is possible by performing all the necessary preventive measures regarding ischemia and stump infection in the prescribed volume and in the development of infectious complications, treatment by the requirements of modern purulent surgery.